Rutin Supplementation Reduces Oxidative Stress, Inflammation and Apoptosis of Mammary Gland in Sheep During the Transition Period - Ding, Hongyan; Li, Yu; Zhao, Chang; Yang, Yue; Xiong, Chengkun; Zhang, Daoliang; Feng, Shibin; Wu, Jinjie; Wang, Xichun (Frontiers in Veterinary Science, 2022)
Rutin, a common dietary flavonoid, exhibits remarkable pharmacological activities such as antioxidant and anti-inflammatory functions. Metabolic stress in mammals during the transition period affects mammary gland health. The aim of this experiment was to evaluate the protective effect of rutin supplementing against metabolic stress in the mammary glands of sheep during the transition period, particularly after parturition. Transition Hu sheep (2-3 years old with 62.90 ± 2.80 kg) were randomly divided into three groups, the control group was fed a diet without rutin, while rutin (50 and 100 mg/kg body weight/day) was administered to the two treatment groups (-28 day to +28 day relative to parturition). Serum and blood samples were collected from jugular vein on days -14, -7, +1, +2, +7, +14, +21, +28 relative to parturition. Mammary tissue biopsy samples of four sheep from the treatment group were harvested on day +28 postpartum. Compared to that in the control group, rutin supplementation resulted in lower β-hydroxybutyrate while increasing the concentrations of non-esterified fatty acids and globulin after lactation. Furthermore, rutin treatment led to lower hydrogen peroxide and malonaldehyde levels, resulting in increased catalase, glutathione peroxidase, superoxide dismutase and total antioxidant potential. Compared to that in the control group, rutin inhibits the mRNA expression of inflammatory markers such as tumor necrosis factor-α (TNF-α). In addition, rutin markedly downregulated the ratio of phosphorylated NF-κB p65 (p-p65) to total NF-κB p65 (p65). Meanwhile, rutin supplementation resulted in high mRNA abundance of the nuclear factor erythroid 2-like 2 (NFE2L2, formerly NRF2) and its target gene, heme oxygenase-1 (HO-1), which plays critical roles in maintaining the redox balance of the mammary gland. Furthermore, rutin treatment lowered the levels of various downstream apoptotic markers, including Bax, caspase3 and caspase9, while upregulating anti-apoptotic Bcl-2 protein. These data indicate the positive effect of rutin against inflammation, oxidative stress status, and anti-apoptotic activity in the mammary gland. The mechanism underlying these responses merits further study.